Ratanlal & Dhirajlal's law of crimes a commentary on the Indian Penal Code, 1860 - Gupta,Shriniwas (Bharat Law House, 2018)
Ratanlal & Dhirajlal's law of crimes a commentary on the Indian Penal Code, 1860 assisted by Smt. M. C. Thakker foreword to the classic's centennial by Hon'ble Mr. Justice V. R. Krishna Iyer